Clinical use, safety and effectiveness of novel high cost anticancer therapies after marketing approval: a record linkage study - Eva Negri; Marta Rossi; Mertina Bonifazi; Matteo Franchi; Greta Carioli; Carlo Zocchetti; Giovanni Corrao; Carlo La Vecchia (Epidemiology, Biostatistics and Public Health)
Background: major clinical outcomes of anticancer drugs may differ between clinical trials and clinical practice. Administrative databases provide long-term information on safety and effectiveness of these drugs in large unselected populations and in selected subgroups of patients. In addition, these data provide complementary information on topics where evidence from randomized clinical trials is unavailable. Methods: this project will investigate 17 new targeted high cost drugs in Lombardy oncology practice between 2006 and 2010 using data from electronic healthcare databases. Specific objectives are: 1) to estimate the incidence of serious adverse events in clinical practice and their predictors; 2) to estimate survival and progression free survival and their predictors; 3) to compare major clinical outcomes according to different regimen of therapy. We will build a database by record linkage of several regional health service sources: the File F registry (in which the administration of the 17 drugs is recorded), the Regional hospital discharge forms (SDO ) database, the drug prescription database, the outpatients' services database, and the Registry Office database. Subjects resident in Lombardy who received at least one prescription of these drugs from 2006 to 2010 will be considered. Complications warranting hospitalization will be derived from the patients' SDO s after the first drug administration. Vital status will be obtained from the Registry Office database. Results: we will provide estimates of the incidence of serious adverse events of novel anticancer therapies, and of overall and disease free survival in clinical practice, overall and in selected subgroups. Conclusions: these data will contribute to a better effectiveness evaluation, particularly in patients under-represented in clinical trials.